1996
DOI: 10.1159/000246229
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma Arising in a Verrucous Epidermal Nevus

Abstract: A 74-year-old Japanese male patient with squamous cell carcinoma arising in an epidermal nevus is described. The patient had widespread warty lesions involving large parts of the body since infancy. Recently, a nodular lesion appeared on the middle part of his back and increased in size. Histologically, the nodule was diagnosed as squamous cell carcinoma and the warty lesion showed the features of epidermal nevus. The nodular lesion was totally excised and the skin defect was covered with split-thickness skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…To the best of our knowledge, only 12 cases of CSCC arising from verrucous epidermal nevi have been reported so far in the literature. Nine cases are displayed in table 1 [7, 12, 13, 14, 15, 16, 17, 18, 19], while the data in the remaining 3 cases were inadequate: 2/3 cases were described in poster abstracts [20, 21], and the third case was not available as a full text [22]. …”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only 12 cases of CSCC arising from verrucous epidermal nevi have been reported so far in the literature. Nine cases are displayed in table 1 [7, 12, 13, 14, 15, 16, 17, 18, 19], while the data in the remaining 3 cases were inadequate: 2/3 cases were described in poster abstracts [20, 21], and the third case was not available as a full text [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Ichikawa et al [21] reported 16 cases of linear epidermal nevi associated with malignant change (BCC, SCC, Bowen's disease, verrucous carcinoma, adnexal carcinoma). In some cases, exposure to physical agents (ultraviolet light and chemical carcinogens) was found to be a predisposing factor.…”
Section: Discussionmentioning
confidence: 99%
“…Some Authors [5,6] have reported that a mild chronic inflammatory infiltrate can be present in the lamina propria. Regarding a possible neoplastic transformation of LEN it is of interest to mention that basal and squamous cell carcinoma, verrucous carcinoma and adnexal carcinoma arised from cutaneous LEN have been reported but, to date, no cases of malignant transformation of oral LEN have been reported [18].…”
Section: Discussionmentioning
confidence: 99%